2017
DOI: 10.1002/ajoc.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Regiochemical Control of Pyrazoles by Solvent and β‐Enamino Diketone Structure: Regioselective Synthesis of 4,5‐Disubstituted N‐Phenylpyrazoles

Abstract: A simple method for the regiocontrolled synthesis of the 4,5‐disubstituted N‐phenylpyrazole regioisomers 2 and 3 from β‐enamino diketones and phenylhydrazine is described. Pyrazole 2 was prepared regioselectively by carrying out the reaction in a protic solvent, whereas pyrazole 3 was obtained as the main product by using an aprotic solvent. Steric factors regarding the β‐enamino diketones also influenced the regiochemistry of 2 and 3. The influence of solvent on the reaction outcome can be rationalized by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Analyzing the reactive potential of the β-enamino diketone systems against arylhydrazine, we observed that the cyclocondensation at C1 and C2’ (carbonyl carbons) would lead to the 3,4,5-trisubstituted N -aryldihydropyrazoles, which upon aromatization via water elimination and subsequent hydrolysis would afford 3,5-disubstituted 4-formyl- N -arylpyrazoles (Scheme , ROUTE D). However, according to the literature the cyclocondensation of β-enamino-diketones with arylhydrazines follows a different regiochemistry, where the C3 (β-carbon) and C1 or C2’ (carbonyl carbons) correspond to the 1,3-dielectrophilic reactive unit, giving 4,5-disubstituted N -arylpyrazoles (Scheme , ROUTE C) . Thus, we report in this letter a one-pot synthetic method that enabled us to control the regiochemistry of the cyclocondensation of β-enamino diketones with arylhydrazines to obtain 3,5-disubstituted 4-formyl and 4-hydroxymethyl N -arylpyrazole derivatives.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Analyzing the reactive potential of the β-enamino diketone systems against arylhydrazine, we observed that the cyclocondensation at C1 and C2’ (carbonyl carbons) would lead to the 3,4,5-trisubstituted N -aryldihydropyrazoles, which upon aromatization via water elimination and subsequent hydrolysis would afford 3,5-disubstituted 4-formyl- N -arylpyrazoles (Scheme , ROUTE D). However, according to the literature the cyclocondensation of β-enamino-diketones with arylhydrazines follows a different regiochemistry, where the C3 (β-carbon) and C1 or C2’ (carbonyl carbons) correspond to the 1,3-dielectrophilic reactive unit, giving 4,5-disubstituted N -arylpyrazoles (Scheme , ROUTE C) . Thus, we report in this letter a one-pot synthetic method that enabled us to control the regiochemistry of the cyclocondensation of β-enamino diketones with arylhydrazines to obtain 3,5-disubstituted 4-formyl and 4-hydroxymethyl N -arylpyrazole derivatives.…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, we have developed synthetic methodologies for the preparation of multifunctionalized N -arylpyrazoles from the modified Knorr reaction using β-enamino diketones and arylhydrazines (Scheme , ROUTE C) . In this context, we envisage that this synthetic strategy would be an attractive one-pot method to obtain 3,5-disubstituted 4-formyl- N -arylpyrazoles, via the regiochemical control of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…First, we chose the BED 1a as a model substrate to evaluate its reactivity against methylhydrazine. As shown in Table , both methodologies previously reported by us afforded a mixture of three regioisomers (A, B, and C) with poor regioselectivity (Table , entries 1 and 2). Then, we further explored the reactivity of the 4-acyl-1 H -pyrrole-2,3-dione Ia , which was generated in situ from BED 2a .…”
Section: Resultsmentioning
confidence: 99%
“…Then, the 4-acyl-1 H -pyrrole-2,3-dione intermediate Ib suffers an intermolecular nucleophilic attack of the secondary amino group of the methylhydrazine on C5, followed by cleavage of the pyrrole ring of IIb to form the acyclic species IIIb . Next, recycling of IIIb to IVb occurs by the attack of the primary amino group on the carbonyl carbon of the α-ketoamide group, followed by water elimination, giving rise to the 3,4-disubstituted N -methylpyrazole 6 . Thus, we suppose that the substrates bearing alkylamino groups do not generate the respective pyrazoles because they do not contribute to the cleavage of the pyrrole ring of IIb to form IIIb .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation